PLANNING AND PRODUCTION CONTROL USING AGGREGATE PLANNING METHOD AT CV. ANTARTIKA IN DENPASAR - Arnoni Arnelita Jonathan; I Nyoman Nurcaya (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Planning and production control using the Aggregate Planning method is carried out to determine the optimal level of production over the medium term, namely 12 months, under fluctuating demand. This study was conducted on the ice tube products of CV. Antartika using the Aggregate Planning method. The study results indicate that the estimated number of products to be produced next year is 32,499 tons, based on the forecast using the Moving Average method, which yielded the smallest standard error estimate of 420.94. The aggregate planning strategy using the Level Strategy resulted in a total estimated production planning cost of IDR 5,129,455,000. This total cost is lower compared to the total production cost using the Chase Strategy for ice tube products. The theoretical implication of this research serves as an additional reference for academics studying aggregate production planning, particularly those employing Level Strategy and Chase Strategy. The practical implication of this research provides the company with considerations for production planning and control over the medium term.